Impact of COVID-19 on Mental Health of Dhaka University Students - Rabby , Md Reza a; Naher, Roufun (Dhaka University Journal of Biological Sciences, 2023)
Student mental health in the university setting has been an expanding concern. The COVID-19 pandemic could be detrimental to the psychological wellness of university students. The aim of this investigation was to see the mental health outcomes of Dhaka University students during the COVID-19 outbreak. A crosssectional survey using a convenient sampling technique was conducted among 193 students of the University of Dhaka within a time duration of 1 month. Data was gathered by utilizing the web survey including DASS-21BV, demographic questions, and health-related queries with respect to COVID-19. The prevalence of anxiety symptoms and depressive symptoms was 64.2 % and 66.9%, respectively, and 51.8% of students reported mild to extremely severe levels of stress. Age group was significantly associated with DASS-21 depression subscale scores (χ2 (2)> =14.179, p= .007). Hall status was also significantly associated with DASS-21 anxiety subscale scores (χ2 (2)> =10.001, p= .040). Sleep-related queries with respect to COVID-19 were significantly associated with DASS-21 anxiety subscale scores (χ2 (2)> =24.135, p= .002). COVID-19-related queries on attention, enthusiasm, mental state, and self-confidencewere also significantly associated with depressive symptoms, anxiety symptoms, and stress levels (p<.001). The COVID-19 outbreak seems to have had a considerable psychological impact on Dhaka University students and would be benefited greatly through adequate support from the relevant authorities to cope with the situation mentally. Dhaka Univ. J. Biol. Sci. 32(1): 45-55, 2023 (January)